Factors that transformed cereals productivity - Abate, T.; Menkir, A.; Belay, G.; Feyissa, R.; Keno, T.; Bossey, O. (2024)
This chapter provides a critical assessment of productivity gains made so far and the opportunities for further improvement ahead for cereals in Ethiopia. Overall, the country achieved a very highly significant yield gain of 92 kg/ha/yr (P<0.01, R2=0.95) between 2000 and 2020 – the fifth highest after Ukraine, Brazil, the USA and Argentina, among the world’s top ten cereal-producing countries. This means that Ethiopia doubled its major cereals productivity during this period. Increases in yield accounted for ~70% of the change in production, compared to ~28% in area expansion. In all of Africa, only South Africa has achieved this level of cereals productivity under rainfed agriculture. The presence of well-functioning institutions, sustained government investment and increased use of mineral fertilizers were some of the factors that contributed to the success.